Pemanfaatan sistem rotary biological contactor menggunakan kultur Omphalina sp yang diimobilisasi pada tandan kosong kelapa sawit untuk absorbsi logam berat Cu2+ dan Hg2+ (Utilization of rotary biological contactor system using Omphalina sp immobilized on oil palm empty fruit bunch for absorption of heavy metals Cu2+ and Hg2+) - Firda DIMAWARNITA; Tri PANJI (E-Journal Menara Perkebunan, 2017)
Heavy metals such as lead, chromium, cadmium, copper, mercury, and arsenic which are industrial by-products can have negative impact on the environment if they not managed properly. Biosorption is environmentally-friendly waste treatment method. The advantage of biosorption compared to other waste treatment method is ecotechnology, which means effective, cheaper than chemical treatment and environmentally-friendly technology. Using the concept of bioremediation-based on microbial enhanced recovery of metals (MERM) allows the possibility of concentration process (bio-concentration) of metal content through the process of biosorption in microbial cells. The process of bio-concentration potentially to be applied on a commercial scale to increase the recovery of high-value commercial metals. This study aims to absorb Cu2 + and Hg2 + metals using Omphalina sp. cultured on empty fruit bunches (EFB) in rotary biological contactor (RBC) systems. The principle of this technique is waste containing metals was contacted with white rot fungi (WRF) Omphalina sp. which is attached to the surface of the media inside a reactor and then the final waste concentration was analyzed. This analysis was using atomic absorption spectrometry (AAS) device to measure the concentration of Cu2+ and Hg2+ metal ions and Freundlich isothermic equations for calculating maximum absorption power (q max). The highest absorption of Cu2+ ion is 0.3304 mg/g and Hg2+ is 0.074 mg/g for 6 hours. The adsorption capacity of Omphalina sp. for Cu2 + and Hg2 + solutions based on the Freundlich adsorption equation with maximum adsorption power for Cu2 + is 71.911 mg/g and Hg2+ is 20.216 mg/g. Biosorbent Omphalina sp. can be reused in biosorption process with percentage decrease of Cu2+ is4.30% (4.3 ppm) and Hg2 + is 27.80% (1.39 ppm) for 18 hours.[Key words : biosorption technique, empty fruit bunches, immobilization, rotary biological contactor , white rot fungi-Omphalina sp.] AbstrakLogam berat seperti timbal, krom, cadmium, tembaga, merkuri, dan arsen yang merupakan hasil samping industri dapat berdampak negatif terhadap lingkungan jika tidak dikelola dengan baik. Biosorpsi merupakan metode pengolahan limbah yang ramah lingkungan.  Keunggulan biosorpsi dibandingkan dengan metode pengolahan limbah yang lainnya adalah ekoteknologi yaitu teknologi efektif, murah dan ramah lingkungan. Melalui konsep bioremediasi berbasis microbial enhanced recovery of metals (MERM) memungkinkan terjadinya proses pemekatan (bio-konsentrasi) kandungan logam melalui proses biosorpsi dalam sel mikroba. Proses bio-konsentrasi tersebut berpeluang untuk diterapkan dalam skala komersial untuk meningkatkan recovery logam bernilai komersial tinggi. Penelitian ini bertujuan untuk meng-absorpsi logam Cu2+ dan Hg2+ menggunakan kultur Omphalina sp. pada media TKKS dalam sistem rotary biological contactor (RBC). Prinsip teknik ini yaitu limbah yang mengandung logam dikontakkan dengan kultur JPP Omphalina sp. yang melekat pada permukaan media di dalam suatu reaktor kemudian konsentrasi limbah akhir dianalisis kandungannya. Analisis ini mengguna-kan alat spektrometri serapan atom (SSA) untuk mengukur konsentrasiion logam Cu2+ dan Hg2+ dan persamaan isoterm Freundlich untuk menghitung daya absorbsi maksimum (q max). Penyerapan tertinggi ion Cu2+ sebesar 0,330 mg/g dan Hg2+ sebesar 0,074 mg/g selama 6 jam. Kapasitas adsorpsi Omphalina sp. terhadap larutan Cu2+ dan Hg2+ berdasarkan persamaan adsorpsi Freundlich dengan daya adsorpsi maksimumnya untuk Cu2+sebesar 71,911 mg/g dan untuk Hg2+ sebesar 20,216 mg/g. Biosorben Omphalina sp. dapat digunakan ulang dalam proses biosorpsi dengan persentase penurunan Cu2+ sebesar 4,30% (4,3 ppm) dan Hg2+ sebesar 27,80% (1,39 ppm) dalam waktu 18 jam.[Kata kunci : imobilisasi, jamur pelapuk putih Omphalina sp, rotary biological contactor, teknik biosorpsi logam, tandan kosong kelapa sawit.]